Serum autoantibodies against a panel of 15 tumor-associated antigens in the detection of ovarian cancer. Issue 6 (May 2017) - Sun, Hao; Shi, Jian-Xiang; Zhang, Hong-Fei; Xing, Meng-Tao; Li, Pei; Dai, Li-Ping; Luo, Cheng-Lin; Wang, Xiao; Wang, Peng; Ye, Hua; Li, Liu-Xia; Zhang, Jian-Ying
In this study, enzyme-linked immunosorbent assay has been used to examine the frequencies of serum autoantibodies against two candidate tumor-associated antigens intensively selected from the Human Protein Atlas database, in combination with 13 tumor-associated antigens available from our lab in sera from 44 OC patients and 50 normal healthy controls. Conventional evaluation (mean + 3SD as the cutoff value to determine a positive reactivity), receiver operating characteristic curve analyses, and classification tree analysis were further used to evaluate the diagnostic performance of autoantibodies against these tumor-associated antigens (anti-tumor-associated antigens) in ovarian cancer. For single anti-tumor-associated antigen, when the cutoff values were set as mean + 3SD of normal healthy controls, NPM1, MDM2, PLAT, p53, and c-Myc could achieve sensitivity higher than 20% at 98% specificity. Combinational utilization of autoantibodies against MDM2, PLAT, NPM1, 14-3-3 Zeta, p53, and RalA achieved the optimal diagnostic performance with 72.7% sensitivity at 96% specificity. Receiver operating characteristic curve analysis showed that the area under the receiver operating characteristic curves of autoantibodies against c-Myc, NPM1, MDM2, p16, p53, and 14-3-3 Zeta were greater than 0.80. This indicated that these tumor-associated antigens held high potential to serve as diagnostic biomarkers in ovarian cancer detection. Decision tree analysis indicated that anti-c-Myc held high potential in the detection of ovarian cancer. Further studies are warranted to validate the diagnostic performance of these anti-tumor-associated antigens with high area under the receiver operating characteristic curve, including autoantibodies against c-Myc, MDM2, PLAT, NPM1, 14-3-3 Zeta, p53, and RalA.